2023
DOI: 10.1177/03635465231183092
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Complications and Associated Variables After High Tibial Osteotomy and Distal Femoral Osteotomy: A 15-Year Experience From a Single Academic Institution

Abstract: Background: High tibial osteotomy (HTO) and distal femoral osteotomy (DFO) are well-recognized treatments to address varus and valgus malalignment, respectively, in the setting of symptomatic unicompartmental arthritis of the tibiofemoral joint. The existing literature is limited in its ability to characterize complications after HTO or DFO procedures. Purpose: The objective of this study was to determine the rate of early (≤90 days) postoperative complications and associated variables from the 15-year experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…To the authors' knowledge, this is the largest reported series of osteotomy around the knee, demonstrating incidence, treatment and successful management of infection with no clear sequelae or impact upon subsequent arthroplasty. In comparison with available recent studies using locking plates, this deep infection rate is lower than the 2% reported by Sidhu et al [25] and 4.1% by Berk et al [3], the former reporting from a series of 200, and the latter 243 osteotomies.…”
Section: Discussioncontrasting
confidence: 54%
“…To the authors' knowledge, this is the largest reported series of osteotomy around the knee, demonstrating incidence, treatment and successful management of infection with no clear sequelae or impact upon subsequent arthroplasty. In comparison with available recent studies using locking plates, this deep infection rate is lower than the 2% reported by Sidhu et al [25] and 4.1% by Berk et al [3], the former reporting from a series of 200, and the latter 243 osteotomies.…”
Section: Discussioncontrasting
confidence: 54%
“…Many complications of distal femoral osteotomy occur in the early postoperative period, with one study showing a ≤90-day complication rate of 42%. 6 Risks for complications or lower survivorship in the literature include smoking, concomitant cartilage or ligament procedures, surgical indication for arthritis, and other medical conditions. 6 , 7 One of the most common complications of a distal femoral osteotomy is symptomatic hardware.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Risks for complications or lower survivorship in the literature include smoking, concomitant cartilage or ligament procedures, surgical indication for arthritis, and other medical conditions. 6 , 7 One of the most common complications of a distal femoral osteotomy is symptomatic hardware. 5 , 8 , 9 The authors aim to limit this complication by their plate-positioning tips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Currently, there are a few publications that have looked at postoperative SSI events following OWHTO. [15][16][17] However, the understanding of its relevant factors is not deep enough. Woodacre et al reported epidemiological data on complications after OWHTO in 115 patients followed for at least 2 years, with a 3.5% incidence of SSI.…”
Section: Introductionmentioning
confidence: 99%